Biodegradable Scaffolds for Cartilage Tissue Engineering: - Mohammadi, Farhad; Ahmadi, Fatemeh; Giti, Rashin; Mohammadi-Samani, Soliman (Galen Medical Journal, 2017)
Being a connective tissue, the cartilage is present in almost all parts of the body like the rib cage, joints, nose, and ear. Its essential function in body is to serve as a cushion between the joints and prevent the bones friction against each other. In some areas like the rib cage, the cartilage keeps the bones together and creates a shockproof area. Osteoarthritis and traumatic rupture of the cartilage are among the related diseases. Damaged cartilage tissue can be only limitedly repaired because of the low density of chondrocyte and slow metabolism in the tissue. Previous studies achieved different outcomes for the joint-preserving treatment programs such as debridement, mosaicplasty, and perichondrium transplantation; however, the average long-term result is still unsatisfactory. The restriction of clinical success is mainly attributed to the long time required in most treatments for the regeneration of new cartilage at the site of defect. The mechanical conditions of these sites makes the repair process unflavored of the original damaged cartilage. Such problems can be permanently treated by using tissue engineered cartilage. Hence, the limitations can be defeated by using appropriate scaffolds, cell sources, and growth factors. This review dealt with the advances in cartilage tissue engineering, with the focus on cell sources, scaffold materials and growth factors used in cartilage tissue engineering.[GMJ.2017;6(2):70-80]